2006
DOI: 10.1002/app.24090
|View full text |Cite
|
Sign up to set email alerts
|

Curing of mixtures of epoxy resins and 4‐methyl‐1,3‐dioxolan‐2‐one with several initiators

Abstract: Diglycidyl ether of bisphenol A or 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate were mixed with different proportions of 4-methyl-1,3-dioxolan-2-one and cured using lanthanide triflates as initiators. In order to compare the materials obtained, conventional initiators such as boron trifluoride complexes and N,N-dimethylaminopyridine were also tested. The curing process was followed by differential scanning calorimetry (DSC) and Fourier transform IR in attenuated total reflectance mode. This techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
(121 reference statements)
1
3
0
Order By: Relevance
“…The macrocycles cannot be detected by spectroscopic procedures but could change the calorimetric characteristics, acting as plasticizers. A similar trend of T g values was obtained in the copolymerization of DGEBA with propylene carbonate with these initiators 21…”
Section: Resultssupporting
confidence: 80%
“…The macrocycles cannot be detected by spectroscopic procedures but could change the calorimetric characteristics, acting as plasticizers. A similar trend of T g values was obtained in the copolymerization of DGEBA with propylene carbonate with these initiators 21…”
Section: Resultssupporting
confidence: 80%
“…DMTMC sample follows the expected trend, whereas in the TMC sample, an increase in this band is followed by a decrease after 2500 s of curing. Because five‐membered cyclic carbonates do not homopolymerize or copolymerize with epoxide in anionic processes,23 the disappearance of this group can only be related to the loss of CO 2 , which leads to the formation of polyether structures 24. By attending to the epoxide absorption at 915 cm −1 , we can see in Figure 4 that all the epoxide groups react although in the DMTMC sample the disappearance is much faster.…”
Section: Resultsmentioning
confidence: 95%
“…These results indicate that whereas CC reacts, PGEC does not polymerize and remain entrapped in the material, similar to the results we obtained with PC. 10 The explanation to the higher reactivity of CC can be found in the higher electrophilic character of its carbonylic carbon, which has a higher d(þ) as is shown in Scheme 4. The aromatic ring directly attached to the oxygens of the carbonate group reduces their electronic density and therefore their electron release effect on the carbonylic carbon.…”
Section: Resultsmentioning
confidence: 95%
“…In a previous paper 10 we reported the curing of mixtures of diglycidylether of bisphenol A (DGEBA) or a cycloaliphatic epoxy resin (ECH) with a cyclic carbonate, 4-methyl-1,3-dioxolane-2-one (PC), using lanthanide triflates or BF 3 ÁMEA as cationic initiators and N,N-dimethylaminopyridine (DMAP) as an anionic initiator with the aim to obtain thermosets with carbonate groups in the polymeric chain and a low shrinkage during curing. However, we observed that the carbonate did not polymerize but remained in the network, acting as a plasticizer, lowering the T g values of the cured materials.…”
Section: Introductionmentioning
confidence: 97%